PENGGUNAAN KALIMAT TUNGGAL DALAM KUMPULAN DONGENG BERBAHASA INDONESIA - Yupita Friskiana Wijaya; Nusarini Nusarini (CARAKA, 2018)
The purpose of this research are (1) to describe the simple sentences type based on the class of words which occupy the predicate, (2) to describe simple sentence pattern, (3 )to describe expansion of the elements in the simple sentences found in the fairytales collection of Indonesian language. Type of this research is a descriptive qualitative research. Data collection techniques in the research by using the simak method then advanced techniques are namely simak bebas libat cakap technique dan noted technique. Data analysis techniques in this research are used agih method with bagi unsur langsung technique, lesap technique, ganti technique, balik technique, and read markah technique. The results of data analysis are informal and formal methods. The results of this study is suggest that (1) a simple sentences type based on the class words that occupy predicate in the fairytales collection namely verbal predicate sentence, nominal predicate sentence, adjectival, prepositional phrase predicate sentences, (2) the general pattern of simple sentences in the collection fairytales of Indonesian language namely S + P + (O) + (Mop) + (Ket) and its realization is S + P, S + P + (Mop), S + P + (O), S + P + (K), S + P + (Mop) + (Ket), S + P + (O) + (Ket), S + P + (O) + (Mop), (Ket) + S + P, (Ket) + S + P + (O) , (Ket) + S + P + (Ket), (Ket) + S + P + (Mop), (Ket) + S + P + (O) + (Ket), (3) expansion of the elements of simple sentences in the fairytales collection is divided into 3 namely the addition of the elements of the description, the addition of the noun vocative, and the addition of apposition.